DESIGN A PROCUREMENT INFORMATION SYSTEM WITH THE RUP METHOD - Leliyanah, Leliyanah; Lestari, Endah Wiji; Dahlia, Dahlia; Herlinawati, Herlinawati (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
For providers of goods/services, goods requirements are a very important component. The need for goods that run out will slow down the performance of the company or agency. Many companies or agencies provide goods procurement services to help meet the demand for other companies goods. A system that is still manual can allow errors in recording, inaccurate data to be created and delays in searching for the necessary data. Computerized system design is an effective and efficient solution in supporting the goods procurement process. Information technology can make costs more effective and procurement systems more innovative.